Description of a new gall-inducing species of Aprostocetus (Hymenoptera: Eulophidae) on Melilotus indicus from Southern Italy - G. Viggiani; R. Monaco (Journal of Entomological and Acarological Research, 2014)
Aprostocetus monacoi Viggiani (Hymenoptera: Eulophidae, Tetrastichinae) is described from stem galls in Melilotus indicus (Fabaceae) from Italy. It is the second native European species of Tetrastichinae known as gall inducer.